Vimentin in mammary gland morphogenesis and contractility during lactation - Thoren, Pinja (My University, 2022)
The mammary gland becomes fully differentiated upon pregnancy and lactation preparing it for nourishing the offspring. Mammary basal epithelial cells lining the ducts and alveoli contract to propel the secreted milk to the nipple. These cells express vimentin intermediate filaments, which have been shown to be involved in development and regulation of cell mechanical strength and movement. While vimentin deficiency was shown to reduce basal epithelial cell proportion and delay ductal outgrowth during pubertal mammary gland development, little is known about the role of vimentin in the lactating mammary gland. In this research project the role of vimentin in basal cell contractility and lactogenic differentiation was explored. The comparison of lactating mammary gland phenotype in wild type (WT) and vimentin knock-out (Vim-/-) mice showed no clear differences, but detailed image analysis revealed a large variation in the alveolar size and disorganised morphology in Vim-/- mammary gland. While milk lipid droplets were fewer but larger inside lactating Vim-/- mammary epithelial cells, the analysis of milk spots and litter weights in the pups of WT and Vim-/- dams demonstrated no significant effects on nursing, suggesting that any defects in lactational differentiation are likely compensated with other mechanisms. Furthermore, no consistent changes in the contractile readout, myosin II phosphorylation, upon vimentin silencing or knockout were detected in human and mouse mammary glands, respectively. This might further reflect the adaptive capacity of the organ to sustain the vital function in mammals. Further details of vimentin in mammary gland function might be detected when examining the actively contracting gland.
Keywords: mammary gland, vimentin, lactation